A review of the United Nations Development Programme Reports on human capital development in Nigeria - EDIH, University Ovuokeroye; Irejeh Enaikpobomene Mina; Faghawari, David Mina (International Journal of Development and Economic Sustainability, 2021)
See article
Keywords: human security; human development; policy formulation; United Nations; Nigeria